Kebijakan Pendidikan Pada Era Industri 4.0 : Proses Pencetakan 100 ribu Wirausaha Baru Jawa Barat - Nurdianto, Daniar Ahmad (Jurnal Inspirasi, 2019)
Abstract The printing of one hundred thousand new entrepreneurs in West Java is the program of the elected Governor of West Java, which was carried out over the last five years, 2013-2018. Implementation of this program is carried out with several procedures such as recruitment, selection, apprenticeship training and mentoring. The "Jabar Masagi" strategy is a collaboration between the Government, Academics, the private sector, business associations, and the media that are the main drivers of the policy process. This research uses qualitative methods, case studies in vocational education in the industrial era 4.0 from the perspective of the policy process. This research explores the characteristics of the formation and implementation of policies that lead to the creation and maintenance of the program. This is a descriptive analysis of what happened, not a prospective study. The research found that the disposition and leadership of the implementing agency are important from a top-down policy. Abstrak Pencetakan seratus ribu wirausaha baru di Jawa Barat adalah program Gubernur Jawa Barat terpilih yang dilaksanakan selama periode lima tahun terakhir, 2013–2018. Implementasi program ini dilakukan dengan beberapa prosedur seperti, perekrutan,seleksi,pelatihan magang dan pendampingan. Strategi “Jabar Masagi”merupakan kolaborasi antara Pemerintah, Akademisi, sektor swasta, asosiasi bisnis, dan media yang menjadi penggerak utama dari proses kebijakan. Penelitian ini menggunakan metode kualitatif, studi kasus dalam pendidikan vokasi di era industri 4.0 dari perspektif proses kebijakan. Penelitian ini mengeksplorasi karakteristik formasi dan implementasi kebijakan yang mengarah pada penciptaan dan pemeliharaan program tersebut. Ini adalah analisis deskriptif tentang apa yang terjadi, bukan studi prespektif. Penelitian menemukan disposisi dan kepemimpinan dari badan pelaksana merupakan hal penting dari sebuah kebijakan top down.